The reliability of ‘development length test and ultimate load test’ on prestress concrete sleepers - Ali, Siti Norbaizura (2012)
The prestressed concrete sleepers are well known on its ability to sustain high loading capacity from train and wagon thus, the use of it has been increased nowadays. This research discusses the bond development and ultimate load test in prestressed concrete sleepers. The deformation of the tendon is low and physically hard to determine by naked eyes compared with the cracking propagation due to bending. The samples are provided by MASTRAK Sdn. Bhd. and tested on Development Length Test and Ultimate Load Test procedure in accordance to Australian Standard 1085.14-2003. The samples were of trapezium cross section with a dimension of 232 mm high 280 mm bottom width 190 mm top width and the length is between 2000 mm and 2006mm.Total of 200 samples have been tested to monitor the bond slippage in the concrete sleepers. Tendon gauge placed at the bottom layer of the tendons was to monitor the deformation of the tendons. The test result shows the slippage in most of the sleepers was less than 0.025mm and was in accordance to the standard. There was not much differs in slippage of tendon 1 and 2 although the load was increased from 186kN to 279kN.The results for each length were compared to identify the critical length of sleepers for maximum slippage to occur. Out of the 200 samples, only two sleepers were found to have a maximum slippage of between 0.005mm and 0.006mm.However, this occurs when the ultimate load was between 413.7 kN and 422.9 kN, which was higher than the design load. Standard cube compression test on 226 samples were also carried out and the result for the standard deviation was 0.44 which was in excellent range of control. Further comparison on ultimate bending moment capacity on the rail seat was made with AS1085.14-2003 and BS 8110 and the results show that they were lower than the experimental value. An empirical analysis had been carried out to analyse the relationship between the experimental and the proposed mathematical model. The comparison between the development length data with previous researchers also show that the experimental value is less than the theoretical method. Thus it proved that the data is reliable.